A Code of Many Colours: A Rationale, Validation and Requirements for a Sound-Based Letter Colour-Code that Might Support Some Children with Dyslexia in Spelling Certain Words - Cramer, Emily (Simon Fraser University, 2015)
Dyslexia is a severe impairment in reading and spelling. Despite receiving best-practice remediation, many children with dyslexia fail to surpass the 30th percentile in reading and spelling. A major impediment to children's remediation is poor attention, which motivates the development of stronger attentional supports. One intriguing candidate is dynamic colour-coding. We have developed a tangible software system (PhonoBlocks), which could leverage dynamic colour-coding. The present study was undertaken to better understand how to use dynamic colours to support children with dyslexia in learning through PhonoBlocks. I develop a theoretical framework for designing dynamic colour-codes and implement and assess it in a mixed-methods study with PhonoBlocks. My framework addresses a general knowledge gap in how to apply dynamic colour to literacy acquisition in software. I use my findings to identify individual and interface factors that affected children’s use of the colours, and recommend general design counter-strategies with specific applications to PhonoBlocks.
Keywords: Riecke; Riecke_2015; Riecke_supervised_thesis; SIAT; alissa-antle; bernhard-riecke; emily-cramer; supervisedThesis; thesis